Transitory and Permanent Cash Flow Shocks in Debt Contract Design - Ma, Le; Sikochi, Anywhere; Xiao, Yajun (Journal of Financial and Quantitative Analysis, 2025)
Abstract We examine how lenders design contracts to account for transitory and permanent cash flow shocks facing borrowers. We find that volatile transitory cash flow shocks are associated with fewer liquidity covenants, indicating financial flexibility that enables firms to survive liquidity crunches. The opposite is true for volatile permanent cash flow, suggesting that borrowers’ economic fundamentals are important credit risk factors. Subsequent analyses show that borrowers exposed to transitory (permanent) shocks face less (more) severe credit consequences following poor performance. Overall, we show that transitory and permanent cash flow shocks have significant and opposite effects on debt contract covenant design.